Pots, farmers and foragers pottery traditions and social interaction in the earliest Neolithic of the lower Rhine area - Vanmontfort, B. (Bart) (Archaeological studies Leiden University, 2010)
"In the study of earliest stage of neolithisation pottery plays a key role. The most advanced north-western settlement in the expansion of the central European Linear Pottery culture during the second half of the sixth millennium B.C. is to be found in the Lower Rhine Area. At the same time this is the northernmost extension of the synchronic and enigmatic pottery groups La Hoguette and Limburg. This volume convincingly states that pottery and its associated habits were among the first of the many new societal aspects to be adopted by neighbouring foraging communities."-- Back cover.